2011
DOI: 10.1130/g31642.1
|View full text |Cite
|
Sign up to set email alerts
|

Seismic slip propagation to the updip end of plate boundary subduction interface faults: Vitrinite reflectance geothermometry on Integrated Ocean Drilling Program NanTro SEIZE cores

Abstract: Seismic faulting along subduction-type plate boundaries plays a fundamental role in tsunami genesis. During the Integrated Ocean Drilling Program (IODP) Nankai Trough Seismogenic Zone Experiment (NanTro SEIZE) Stage 1, the updip ends of plate boundary subduction faults were drilled and cored in the Nankai Trough (offshore Japan), where repeated large earthquakes and tsunamis have occurred, including the A.D. 1944 Tonankai (Mw = 8.1) earthquake. Samples were obtained from the frontal thrust, which connects the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(140 citation statements)
references
References 15 publications
6
130
1
Order By: Relevance
“…Unit III is characterized by a fractured and brecciated zone, and the fault zone within Unit III was sampled at 271 mbsf, where it consists of microbreccia and a narrow dark layer ~1 cm thick that dips at 50° to the core vertical axis (Expedition 316 Scientists, 2009a). Analyses of this fault sample revealed evidence for frictional heat, including an increase in vitrinite reflectance, enrichment in Al and K and depletion in Ca and Sr, and an increase in illite crystallinity, implying possible propagation of seismic slips to this shallow portion of the megasplay branch fault (Yamaguchi et al, 2011;Sakaguchi et al, 2011a). In addition, the top 1 m of core contains repeated occurrences of earthquake-induced mud breccia, the uppermost of which was found by 210 Pb dating to have been deposited at the time of the 1944 Tonankai earthquake (Sak-…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Unit III is characterized by a fractured and brecciated zone, and the fault zone within Unit III was sampled at 271 mbsf, where it consists of microbreccia and a narrow dark layer ~1 cm thick that dips at 50° to the core vertical axis (Expedition 316 Scientists, 2009a). Analyses of this fault sample revealed evidence for frictional heat, including an increase in vitrinite reflectance, enrichment in Al and K and depletion in Ca and Sr, and an increase in illite crystallinity, implying possible propagation of seismic slips to this shallow portion of the megasplay branch fault (Yamaguchi et al, 2011;Sakaguchi et al, 2011a). In addition, the top 1 m of core contains repeated occurrences of earthquake-induced mud breccia, the uppermost of which was found by 210 Pb dating to have been deposited at the time of the 1944 Tonankai earthquake (Sak-…”
Section: Background and Objectivesmentioning
confidence: 99%
“…The megasplay fault branches in the shallower part; one section reaches the ocean bottom and the other connects to the decollement beneath the toe of the accretionary prism (Tsuji et al 2014). Both branches are considered to have slipped during past megathrust earthquakes (Sakaguchi et al 2011;Tsuji et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Slip inversion studies suggest that only in this region did past coseismic rupture clearly extend shallow enough for drilling (Ichinose et al, 2003;, and an updip zone of large slip has been identified and targeted. Notably, coseismic slip during events like the 1944 Tonankai earthquake may have occurred on the megasplay fault in addition to the plate boundary décollement (Ichinose et al, 2003;Baba et al, 2006;Sakaguchi et al, 2011). The megasplay fault is therefore a primary drilling target equal in importance to the basal décollement.…”
Section: Geological Settingmentioning
confidence: 99%
“…F1). Several lines of evidence indicate that the megasplay system is geologically active and may participate in coseismic slip (e.g., Sakaguchi et al, 2011). However, the partitioning of strain between the décollement zone and the megasplay system ( Fig.…”
Section: Introductionmentioning
confidence: 99%